Revision of the Oriental Chaetocnema species (Coleoptera, Chrysomelidae, Galerucinae, Alticini) - Ruan, Yongying; Yang, Xingke; Konstantinov, Alexander S.; Prathapan, Kaniyarikkal D.; Zhang, Mengna (Zootaxa, 2019)
The Oriental species of Chaetocnema Stephens, 1831 are revised. There are 85 valid species, including 19 new species: C. angustifrons sp. nov.; C. appendiculata sp. nov.; C. baoshanica sp. nov.; C. dapitanica sp. nov.; C. glabra sp. nov.; C. greenica sp. nov.; C. jinxiuensis sp. nov.; C. hongkongensis sp. nov.; C. latapronota sp. nov.; C. midimpunctata sp. nov.; C. nigrilata sp. nov.; C. parafusiformis sp. nov.; C. paragreenica sp. nov.; C. paraumesaoi sp. nov.; C. purerulea sp. nov.; C. reteimpunctata sp. nov.; C. sabahensis sp. nov.; C. subbasalis sp. nov.; C. trapezoida sp. nov. Fifteen new synonyms are proposed: C. assamensis Scherer, 1969 (syn. nov.) = C. hainanensis Chen, 1932; C. birmanica Jacoby, 1892 (syn. nov.) = C. malayana Baly, 1877; C. ebenina Warchalowski, 1973 (syn. nov.) = C. yiei Kimoto, 1970; C. flavipennis Medvedev, 1996 (syn. nov.) = C. granulicollis Jacoby, 1896; C. harita Maulik, 1926 (syn. nov.) = C. westwoodi Baly, 1877; C. himalayana Medvedev, 1993 (syn. nov.) = C. melonae Chen, 1934; C. kwangsiensis Chen, 1939 (syn. nov.) = C. hainanensis Chen, 1932; C. loriae Jacoby, 1905 (syn. nov.) = C. nigrica Motschulsky, 1858; C. nepalensis Scherer, 1969 (syn. nov.) = C. bella Baly, 1877; C. nitens Baly, 1877 (syn. nov.) = C. nigrica Motschulsky, 1858; C. placida Jacoby, 1896 (syn. nov.) = C. bella Baly 1877; C. shanensis Bryant, 1939 (syn. nov.) = C. bella Baly 1877; C. subcostata Jacoby, 1889 (syn. nov.) = C. wallacei Baly, 1877; C. vietnamica Chen & Wang, 1980 (syn. nov.) = C. modigliani Jacoby, 1896; C. vietnamica Medvedev, 2009 (syn. nov.) = C. wallacei Baly, 1877. C. vietnamica Medvedev, 2001 is a new junior homonym of C. vietnamica Chen & Wang, 1980. C. melonae Chen, 1934 status restored and resurrected from synonymy with C. duvivieri Jacoby, 1892 in Medvedev, 2001: 613. Two subspecies are raised to species level: C. taiwanensis Chûjô, 1965 new status for C. tonkinensis taiwanensis Chûjô, 1965 and C. yunnanica Heikertinger, 1951 new status for C. discreta yunnanica Heikertinger, 1951. Lectotypes are designated for 25 species: C. minuta Jacoby, 1896; C. granulicollis Jacoby, 1896; C. kwangsiensis Chen, 1939; C. longipunctata Maulik, 1926; C. montivaga Maulik, 1926; C. basalis Baly, 1877; C. parvula Baly, 1877; C. nitens Baly, 1877; C. geniculata Jacoby, 1896; C. simplicifrons (Baly, 1876); C. sticta Maulik, 1926; C. sumatrana Jacoby, 1896; C. wallacei Baly, 1877; C. alticola Maulik, 1926; C. belli Jacoby 1904; C. cognata Baly, 1877; C. squarrosa Baly, 1877; C. concinnipennis Baly, 1877; C. malayana Baly, 1877; C. birmanica Jacoby, 1892; C. merguiensis Bryant, 1941; C. pusaensis Maulik, 1926; C. singala Maulik, 1926; C. westwoodi Baly, 1877; C. harita Maulik, 1926.